Survey of spinal cord injury-induced neurogenic bladder studies using the Web of Science - Zou, Benjing; Zhang, Yongli; Li, Yucheng; Wang, Zantao; Zhang, Ping; Zhang, Xiyin; Wang, Bingdong; Long, Zhixin; Wang, Feng; Song, Guo; Wang, Yan (Neural regeneration research, 2012)
OBJECTIVE：To identify global trends in research on spinal cord injury-induced neurogenic bladder, through a bibliometric analysis using the Web of Science. DATA RETRIEVAL：We performed a bibliometric analysis of studies on spinal cord injury-induced neurogenic bladder using the Web of Science.Data retrieval was performed using key words＂spinal cord injury＂,＂spinal injury＂,＂neurogenic bladder＂,＂neuropathic bladder＂,＂neurogenic lower urinary tract dysfunction＂,＂neurogenic voiding dysfunction＂,＂neurogenic urination disorder＂and ＂neurogenic vesicourethral dysfunction＂. SELECTION CRITERIA：Inclusion criteria：（a）published peer-reviewed articles on spinal cord injury-induced neurogenic bladder indexed in the Web of Science;（b）type of articles：original research articles and reviews;（c）year of publication：no limitation.Exclusion criteria：（a）articles that required manual searching or telephone access;（b）Corrected papers and book chapters. MAIN OUTCOME MEASURES：（1）Annual publication output;（2）distribution according to journals; （3）distribution according to subject areas;（4）distribution according to country;（5）distribution according to institution;and（6）top cited publications. RESULTS：There were 646 research articles addressing spinal cord injury-induced neurogenic bladder in the Web of Science.Research on spinal cord injury-induced neurogenic bladder was found in the Science Citation Index-Expanded as of 1946.The United States,Ireland and Switzerland were the three major countries contributing to studies in spinal cord injury-induced neurogenic bladder in the 1970s.However,in the 1990s,the United States,the United Kingdom,the Netherlands,Germany and Japan published more papers on spinal cord injury-induced neurogenic bladder than Switzerland,and Ireland fell off the top ten countries list.In this century,the United States ranks first in spinal cord injury-induced neurogenic bladder studies,followed by France,the United Kingdom,Germany,Switzerland and Japan.Subject categories including urology, nephrology and clinical neurology,as well as rehabilitation,are represented in spinal cord injury-induced neurogenic bladder studies. CONCLUSION：From our analysis of the literature and research trends,we conclude that spinal cord injury-induced neurogenic bladder is a hot topic that will continue to generate considerable research interest in the future.